The Legal Language: Its Definitions and Applications in the Arabs Laws - Adil Elshiekh Abdalla Ahmed (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2021)
This study deals with the definition of the legal language, its characteristics, its patterns and relationship to the general language, with the application of that in the Arabic language. The study paid attention to its applications in the Arabic language due to laxity of this type of language in the area of teaching Arabic. The study follows the descriptive analytical approach. The data of the legal document subjected to analysis and collected randomly from Arab legal and legislative publications. As the study shows, the legal language characterized with certain features that turned it to be different from the rest of the other types of language. These distinctive elements include amongst others: strangeness, ambiguity, excessive length of the sentence. Consequently, it seems to be too difficult and incomprehensible for those who are not specialized in laws, even though it is of the same normal language, and is subject to its phonemic, grammatical and semantic rules.: ØªØªÙ†Ø§ÙˆÙ„ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ØªØ¹Ø±ÙŠÙ Ø§Ù„Ù„ØºØ© Ø§Ù„Ù‚Ø§Ù†ÙˆÙ†ÙŠØ© ÙˆØ®ØµØ§Ø¦ØµÙ‡Ø§ ÙˆØ£Ù†Ù…Ø§Ø·Ù‡Ø§ ÙˆØ¹Ù„Ø§Ù‚ØªÙ‡Ø§ Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø§Ù…Ø© Ù…Ø¹ ØªØ·Ø¨ÙŠÙ‚ Ø°Ù„Ùƒ ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. ÙˆÙ‚Ø¯ Ø§Ù‡ØªÙ…Øª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¨ØªØ·Ø¨ÙŠÙ‚Ø§ØªÙ‡Ø§ ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø³Ø¨Ø¨ ØªØ±Ø§Ø®ÙŠ Ù‡Ø°Ø§ Ø§Ù„Ù†ÙˆØ¹ Ù…Ù† Ø§Ù„Ù„ØºØ© ÙÙŠ Ù…Ø¬Ø§Ù„ ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. ØªØªØ¨Ø¹ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠ. ÙŠØªÙ… Ø¬Ù…Ø¹ Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„ÙˆØ«ÙŠÙ‚Ø© Ø§Ù„Ù‚Ø§Ù†ÙˆÙ†ÙŠØ© Ø§Ù„Ø®Ø§Ø¶Ø¹Ø© Ù„Ù„ØªØÙ„ÙŠÙ„ Ø¨Ø´ÙƒÙ„ Ø¹Ø´ÙˆØ§Ø¦ÙŠ Ù…Ù† Ø§Ù„Ù…Ø·Ø¨ÙˆØ¹Ø§Øª Ø§Ù„Ù‚Ø§Ù†ÙˆÙ†ÙŠØ© ÙˆØ§Ù„ØªØ´Ø±ÙŠØ¹ÙŠØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. ÙƒÙ…Ø§ ØªÙˆØ¶Ø Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ØŒ ØªØªÙ…ÙŠØ² Ø§Ù„Ù„ØºØ© Ø§Ù„Ù‚Ø§Ù†ÙˆÙ†ÙŠØ© Ø¨Ø³Ù…Ø§Øª Ù…Ø¹ÙŠÙ†Ø© Ø¬Ø¹Ù„ØªÙ‡Ø§ Ù…Ø®ØªÙ„ÙØ© Ø¹Ù† Ø¨Ø§Ù‚ÙŠ Ø£Ù†ÙˆØ§Ø¹ Ø§Ù„Ù„ØºØ§Øª Ø§Ù„Ø£Ø®Ø±Ù‰. ØªØ´Ù…Ù„ Ù‡Ø°Ù‡ Ø§Ù„Ø¹Ù†Ø§ØµØ± Ø§Ù„Ù…Ù…ÙŠØ²Ø© Ù…Ù† Ø¨ÙŠÙ† Ø£Ù…ÙˆØ± Ø£Ø®Ø±Ù‰: Ø§Ù„ØºØ±Ø§Ø¨Ø© ØŒ ÙˆØ§Ù„ØºÙ…ÙˆØ¶ ØŒ ÙˆØ·ÙˆÙ„ Ø§Ù„Ø¬Ù…Ù„Ø© Ø§Ù„Ù…ÙØ±Ø·. ÙˆØ¨Ø§Ù„ØªØ§Ù„ÙŠ ØŒ ÙŠØ¨Ø¯Ùˆ Ø£Ù†Ù‡ ØµØ¹Ø¨ Ù„Ù„ØºØ§ÙŠØ© ÙˆØºÙŠØ± Ù…ÙÙ‡ÙˆÙ… Ø¨Ø§Ù„Ù†Ø³Ø¨Ø© Ù„Ø£ÙˆÙ„Ø¦Ùƒ ØºÙŠØ± Ø§Ù„Ù…ØªØ®ØµØµÙŠÙ† ÙÙŠ Ø§Ù„Ù‚ÙˆØ§Ù†ÙŠÙ† ØŒ Ø¹Ù„Ù‰ Ø§Ù„Ø±ØºÙ… Ù…Ù† Ø£Ù†Ù‡Ø§ Ù…Ù† Ù†ÙØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø§Ø¯ÙŠØ© ØŒ ÙˆØªØ®Ø¶Ø¹ Ù„Ù‚ÙˆØ§Ø¹Ø¯Ù‡Ø§ Ø§Ù„ØµÙˆØªÙŠØ© ÙˆØ§Ù„Ù†ØÙˆÙŠØ© ÙˆØ§Ù„Ø¯Ù„Ø§Ù„ÙŠØ©.